2021
DOI: 10.1039/d1fo00467k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cranberry beverages on oxidative stress and gut microbiota in subjects with Helicobacter pylori infection: a randomized, double-blind, placebo-controlled trial

Abstract: Helicobacter pylori-induced oxidative stress plays an important role in gastric diseases. H. pylori disturbs gut microbiota. The objective is to investigate the effects of cranberry beverages on oxidative stress biomarkers...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Cochrane's risk-of-bias tool for randomized trials is a standard tool used to evaluate the quality of RCTs [18]. Two authors individually assessed each included study using the following seven main aspects of the Cochrane risk-of-bias tool one by one: (1) random sequence generation (selection bias); (2) allocation concealment (selection bias); (3) blinding of participants and personnel (performance bias); (4) blinding of outcome assessment (detection bias); (5) incomplete outcome data (attrition bias); (6) selective reporting (reporting bias); (7) other bias. Based on the evaluation criterion of Cochrane's recommendations, the overall risk-of-bias judgment of each aspect was classified as "high risk", "unclear risk", and "low risk".…”
Section: Quality Assessment Of Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane's risk-of-bias tool for randomized trials is a standard tool used to evaluate the quality of RCTs [18]. Two authors individually assessed each included study using the following seven main aspects of the Cochrane risk-of-bias tool one by one: (1) random sequence generation (selection bias); (2) allocation concealment (selection bias); (3) blinding of participants and personnel (performance bias); (4) blinding of outcome assessment (detection bias); (5) incomplete outcome data (attrition bias); (6) selective reporting (reporting bias); (7) other bias. Based on the evaluation criterion of Cochrane's recommendations, the overall risk-of-bias judgment of each aspect was classified as "high risk", "unclear risk", and "low risk".…”
Section: Quality Assessment Of Meta-analysismentioning
confidence: 99%
“…The role of cranberry in preventing urinary tract infections in both adults and children has been widely acknowledged [ 3 ]. Some researchers now believe that cranberry can protect against cardiovascular diseases, reduce the risk of various cancers and metabolic diseases, and even prevent tooth decay, periodontitis, and Helicobacter pylori [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…salivarius on microbial counts and survival to in vitro digestion, where the results indicated that the inhibition of H. pylori growth was produced in all juices. Recently, Gao et al [ 98 ] studied the effect of cranberry juice consumption (240 and 480 mL of juice, and 480 mL of placebo) on oxidative stress biomarkers and patients affected by H. pylori infection. The blood results indicated that cranberry juice remodeled the gut microbiota of the hospitalized patients, since the juice decreased the growth of H. pylori .…”
Section: Anti- Helicobacter Pylori Effects Of Plant-based Polyphenolsmentioning
confidence: 99%
“…Cranberry ( Vaccinium macrocarpon ) is a natural food and medicinal plant that has attracted much attention in recent years because of its unique health and medicinal effects. It is currently widely used in powder and extract forms in a variety of food and nutritional supplements ( 19 , 20 ). Some studies have shown that high concentrations of cranberry polyphenols are associated with antibacterial, antiviral, anti-inflammatory and antioxidant properties ( 21–24 ).…”
Section: Introductionmentioning
confidence: 99%